People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Regulation and Supervision of Secondary Markets. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2021)
Hong Kong SAR has, over the recent years, become an equity trading hub catering to domestic and foreign investors, including increasingly to investors from Mainland China. Most trading is conducted on markets operated by recognized exchange companies, with limited domestic trading happening via automated trading services (ATS) providers in the form of alternative liquidity pools. The introduction of Stock Connect in 2014 enabled investors from Hong Kong (including domestic and foreign) to directly invest in the Shanghai and later Shenzhen markets and investors from the Mainland to directly access the Hong Kong market. Trading via Stock Connect has seen a steady rise over the last few years, increasing the linkages between Hong Kong SAR and the Mainland. Mainland companies currently account for over 60 per cent of market capitalization of the equities traded on the Stock Exchange of Hong Kong (SEHK).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Hong Kong Special Administrative Region, People's Republic of China